2009
DOI: 10.4049/jimmunol.0801986
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Promotes Th17 Cell Development through Inhibition of SOCS3

Abstract: TGF-β, together with IL-6 and IL-21, promotes Th17 cell development. IL-6 and IL-21 induce activation of STAT3, which is crucial for Th17 cell differentiation, as well as the expression of suppressor of cytokine signaling (SOCS)3, a major negative feedback regulator of STAT3-activating cytokines that negatively regulates Th17 cells. However, it is still largely unclear how TGF-β regulates Th17 cell development and which TGF-β signaling pathway is involved in Th17 cell development. In this report, we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
158
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(164 citation statements)
references
References 32 publications
3
158
1
2
Order By: Relevance
“…Interestingly, in contrast to previous studies showing an inhibitory role for SOCS3 in Th17 differentiation (35)(36)(37), a recent study by Kleinsteuber et al (38) found that overexpression of SOCS3 in human memory T cells promotes IL-17 production. A possible explanation for this discrepancy is that the role of SOCS3 is different in Th17 polarization versus activation of memory T cells that may be precommitted to a Th17 phenotype.…”
Section: Discussioncontrasting
confidence: 43%
“…Interestingly, in contrast to previous studies showing an inhibitory role for SOCS3 in Th17 differentiation (35)(36)(37), a recent study by Kleinsteuber et al (38) found that overexpression of SOCS3 in human memory T cells promotes IL-17 production. A possible explanation for this discrepancy is that the role of SOCS3 is different in Th17 polarization versus activation of memory T cells that may be precommitted to a Th17 phenotype.…”
Section: Discussioncontrasting
confidence: 43%
“…IL-17, IL-23, and IL-1␤ promote production of IL-6, IL-21, and transforming growth factor beta (TGF-␤) (35,52), the key differentiation factors for Th17 cells (7,43,48,63). For these reasons, we thought it was important to determine the source of this early IL-17 production and the conditions that prompted it.…”
Section: Discussionmentioning
confidence: 99%
“…The TGF--mediated signal inhibits IL-6-induced SOCS3 promoter activity and prolongs STAT3 activation. 19) Activated STAT3 is known to bind IL-17A and IL17F promoter and amplifies the RORtdependent differentiation of Th17 cells. 18,20,21) All transretinoic acid (ATRA) inhibits Th17 polarization via upregulation of FoxP3, in a STAT3 independent manner.…”
Section: Discussionmentioning
confidence: 99%